NUMERICAL MODELING OF MF4 RESERVOIR BASED ON SEDIMENTARY MODEL OF SH-6 â SH-7 INTERVAL, SHALLOW ZONE, MERDEKA FIELD, EAST KALIMANTAN - Priyadi, Yogi
Shallow Zone of Merdeka Field were started to develop to mitigate production decline due to its hydrocarbon potential and specific geological characters. Well log data and seismic attributes were the main elements in facies interpretation supported by cores and regional geological setting understanding, all together integrated in order to generate a conceptual sedimentary model. MF6-Beta interval (3rd A conceptual sedimentary model was used as a reference in numerical modeling when constructing a skeleton and stratigraphy and sedimentology grids, in order to preserve reservoir heterogeneity while doing properties propagation by combination of stochastic and deterministic methods. order sequence) was characterized by upward channel sandstone development (regression), meanwhile in parasequence scale showed a repetition of shallowing and deepening upward pattern characterized by limestone appearance at the end of depositional episode, and amalgamated fluvial channel as MF4 main reservoir appeared at the maximum progradation phase. This research proved that geological concept was obligatory as a main control in numerical modeling.